169k views
0 votes
Solve.(z-2)(z-1)=0(If there is more than one solution, separate them with commas.)= 0Z=80,0,...Ś

Solve.(z-2)(z-1)=0(If there is more than one solution, separate them with commas.)= 0Z-example-1
User On
by
5.5k points

1 Answer

4 votes

We have the equation:


(z-2)(z-1)=0

There are a total of two options that complies the equation, as it is a product.

If the first term is 0, the equation is right.

But if the second term is 0, the equation is right too.

Then both are solutions.

So we have:


z-2=0
z=2

And,


z-1=0
z=1

Then we can conclude:

The two correct answers are z=2 and z=1

z=1,2 in the format asked.

User Bchetty
by
5.3k points